Treponema diversity in root canals with endodontic failure - Nóbrega, Leticia M. M.; Delboni, Maraisa G.; Martinho, Frederico C.; Zaia, Alexandre A; Ferraz, Caio C. R.; Gomes, Brenda P. F. A. (European Journal of Dentistry, 2013)
Objective: This study sought to investigate the prevalence of eight oral Treponemas (Treponema denticola, T. amylovorum, T. maltophilum, T. medium, T. pectinovorum, T. socranskii, T. vicentii and T. lecithinolyticum) in teeth with endodontic treatment failure and periapical lesion.Methods: Samples were taken from 40 root canals presenting endodontic failure and periapical lesion. DNA extraction was performed and Nested-PCR technique was used for the detection of Treponema species using specific primers.Results: Treponemas was detected in 56.5% of the samples analyzed (22/39). Individual root canals yielded a maximum of 6 target Treponema species. T. denticola (30.8%) and T. maltophilum (30.8%) were the most frequently detected species followed by T. medium (20.5%), T. socranskii (20.5%), T. pectinovorum (17.9%) and T. vicentii (17.9%). Positive association was verified between T. denticola and T. maltophilum such as T. medium (P<.05). T. lecithinolyticum was positively associated with intraradicular post (P<.05).Conclusion: The present study revealed that a wide variety of Treponema species plays a role in persistent/secondary infection turning the root canal microbiota even more complex than previously described by endodontic literature. (Eur J Dent 2013;7:61-68)
Keywords: Endodontic failure; microbiology; nested-PCR; acteria; root canal